Phytopharmaceuticals and phytochemicals evaluation on leaves and bark of Calophyllum inophyllum and Calophyllum soulatri - SRI BUDI SULIANTI; EMMA SRI KUNCARI; SOFNIE M. CHAIRUL (Biodiversitas Journal of Biological Diversity, 2006)
Phytopharmaceuticals and phytochemicals evaluation on two species of Calophyllum (C. inophyllum and C. soulatri) had been done. Phytopharmaceuticals had been carried out by macro- and microscopic observation and also phytochemical screening by Ciuley Method (1984). Macromorphology of two species of Calophyllum was quite different. Leaf surface of C. inophyllum were obovate lamina, entire margin, obtuse apex, symmetrically base, petiole 1.5-2.0 cm, upper surface were green, shine, glabrous, occurrence of oil gland, and lower surface were long (hirsute), midrib, pinnate venation. C. soulatri were ovate lamina, entire margin, acute apex, symmetrically base, petiole 1.5-2.0 cm, upper surface were green but not shine, glabrous, no occurrence of oil glands and lower surface were long (hirsute), midrib, pinnate venation, green, and glabrous. Leaf dimension of C. inophyllum (± 20x10 cm2) was wider than C. soulatri (± 10x5 cm2). Leaf micromorphology of two species was also different in stomata type, C. inophyllum was paracytic type while C. soulatri was anisocytic type. Oil glands in C. inophyllum were higher than C. soulatri. There were no hair glands that found in these species. Micromorphology bark identified of two species showed that the number of oil glands in C. inophyllum is more than C. Soulatri, Ca oxalate of C. inophyllum is in simple and twin forms which C. soulatri is loose aggregates of numerous prisms which have grown together to form a roughly spherical mass which has projecting points and angles all over surface. Phytochemical screening identified that these species contents are have similar chemical groups (volatile oil, fatty acids, steroids/ triterpenes, tannin, flavonoids and reducing sugar). © 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: Calophyllum inophyllum, C. soulatri, Clusiaceae, phytopharmaceuticals and phytochemicals evaluation.